Servant Leadership's Impact on Adaptive Performance in Indonesian Tech Companies: How Work Engagement and Trust in Leaders Play a Role - Utami, Ayu Rizky; Ardiyanti, Niken (The Asian Journal of Technology Management (AJTM), 2023)
Abstract. Numerous technology-based companies have emerged in Indonesia due to the rapid growth of the technology sector over the last decades. Employees are required to be more adaptive to help the company succeed. Identifying which factors affect employees to adapt in a dynamic and competitive industry is essential. However, study related to adaptive performance affected by servant leadership among technology companies’ employees is still limited, particularly in Indonesia. Thus, this research is expected to contribute by providing new knowledge and literature for academics, especially in the field of human resources, as well as other areas related to employee performance, leadership, work engagement, and trust in leaders. Using the structural equation model with Lisrel 8.8 version, we provide the linkages on how work engagement and trust in leaders mediate the effect of servant leadership on adaptive performance of technology companies’ employees in Indonesia. The data (N=333) was collected from employees working in Indonesia’s technology sector such as financial technology, e-commerce, online transportation and food delivery, online travel, and so forth. Our findings showed that servant leadership has a significant and positive effect on adaptive performance through work engagement. However, trust in leaders does not have a positive mediating effect. Thus, it is important for management in the company to encourage the implementation of servant leadership and assess employees’ work engagement on a timely basis to boost employees’ adaptive performance. Keywords:  Adaptive performance, servant leadership, technology companies, trust in leader, work engagement